Biochemistry illustrated - Campbell, P. N. 4 0 (Peter Nelson)16; (Anthony Donald), 1926- Smith, Anthony D.; 5 (Edinburgh ;;New York : Churchill Livingstone, 2000)
Useful for exam preparation, this text presents biochemistry that is relevant to medical students in a highly graphical style with the minimum of text.
1. The cellular basis of biochemistry -- 2. An introduction to proteins and peptides -- 3. Nucleic acids and protein synthesis -- 4. Protein structure and function with hemoglobin as an example -- 5. Proteins: specialized functions -- 6. The structure and function of enzymes -- 7. Carbohydrate structures and their interconversions -- 8. Nitrogen metabolism -- 9. Oxidative catabolism of glucose and fatty acids -- 10. Carbohydrate and lipid metabolism in the fasting state -- 11. Carbohydrate and lipid metabolism in the absorptive state -- 12. Plasma lipoproteins, cholesterol metabolism and atherosclerosis.
Includes index.
Includes bibliographical references (p. vii-xv) and index.
Keywords: 2 -- 0; 6; Biochemistry;Biyokimya;Biochemistry.;Biochemistry -- 20 -- Outlines.;Anahatlar.;Outlines, syllabi, etc; 20; 2